Single dosing comparison of the relative cardiac beta 1/beta 2 activity of inhaled fenoterol and salbutamol in normal subjects. Issue 6 (June 1993) - Newnham, D M; Wheeldon, N M; Lipworth, B J; McDevitt, D G
Abstract : BACKGROUND--The aim of the present study was to compare the dose related effects of fenoterol and salbutamol on cardiac beta 1 and beta 2 receptors using the beta 1 selective antagonist atenolol, in order to dissect out relative beta 1/beta 2 mediated responses. METHODS--Fourteen normal volunteers were randomised to receive pretreatment with either atenolol 25 mg or placebo, followed by inhaled fenoterol or salbutamol in equal doses by weight (cumulative doses of 1 mg and 4 mg). Measurements were made 30 minutes after inhaling each dose of beta 2 agonist. Values (mean and 95% CI) were expressed as a change from baseline. RESULTS--At 4 mg fenoterol produced equivalent falls in serum potassium and increases in tremor to salbutamol. The mean (95% CI) increase in heart rate (beats/min) with fenoterol at 4 mg after placebo was 47 (41-53) and after atenolol was 34 (28-40), with values for salbutamol being 46 (40-52) after placebo and 30 (24-36) after atenolol. The inotropic response (stroke distance) after atenolol at the 4 mg dose was 5.0 (3.9-6.1) cm for fenoterol and 4.7 (3.5-5.9) cm for salbutamol. There were no significant differences in heart rate or stroke distance response between the two drugs after either placebo or atenolol. Furthermore, ECG effects (Q-Tc and T wave) of fenoterol and salbutamol were comparable at both doses. CONCLUSIONS--These results show that there is no difference in the respective chronotropic or inotropic activities of fenoterol and salbutamol on cardiac beta 1 or beta 2 receptors when given at higher than conventional doses.